The Effect of Discipline, Motivation, Work Environment on Employee Performance and Their Impact on Job Satisfaction Employees at Bank Muamalat Tulungagung Branch Office - Puryanti, Anggi Putri; Supriyadi, Ahmad; Rafikasari, Elok Fitriani (El-Qist: Journal of Islamic Economics and Business (JIEB), 2023)
This study examines the influence of discipline, motivation, and work environment on employee performance and their indirect effect on job satisfaction at Bank Muamalat Tulungagung Branch Office. Using a quantitative explanatory design with path analysis, data were collected from all 30 employees using a saturated sampling technique. The results show that all three independent variables significantly impact employee performance, both directly and indirectly through job satisfaction. Notably, the work environment exerted the strongest direct influence on performance, while job satisfaction served as a significant mediating variable, contributing to 72.9% of the variance in performance. The study contributes to international human resource and Islamic organizational behavior literature by integrating job satisfaction as a key mediating construct in performance enhancement within Islamic financial institutions. It highlights how discipline rooted in Shariah values, intrinsic motivation, and supportive environments shape optimal employee outcomes. This research provides a foundational model for Islamic HR performance frameworks that can be tested across global Islamic banking settings. Future studies may compare the mediating role of satisfaction across different cultural and regulatory environments or incorporate Islamic leadership and spiritual motivation as additional variables in performance modeling.